Statistical Analysis of 194 Colonic Resections -Anastomosis in 176 Patients - Armand Ugon, Alfredo; Besenzoni, Raúl; Harretche, Martín (Cirugía del Uruguay, 1979)
194 colonic resections - anastomosis are analyzed with special emphasis en those aspects which account for Suture í'ailure. Incidence increases in cases of advanced age, neoplastic etiology, use of chromisized catgut, suture in more. than two layers, left resections and termino - terminal reconstruction.